2020
DOI: 10.1108/jea-06-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

How aspiring principals applied course-based learning to develop school improvement plans

Abstract: PurposeSchool improvement planning and implementation is one organizational process by which principals may positively impact school and student outcomes. Limited research, however, has explored how principal preparation programs prepare aspiring leaders for this common school leadership activity. This study examined aspiring principals engaged in the school improvement process by evaluating what they included in their school improvement plans (SIPs) that were developed as part of their field experience.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…This choice aligns with the claim that principals wield significant influence in driving school improvement and implementing transformative changes (Bickmore et al ., 2021). The complex and challenging nature of school leadership necessitates that principals prioritize learning-centered approaches within their schools (Knapp et al ., 2014).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This choice aligns with the claim that principals wield significant influence in driving school improvement and implementing transformative changes (Bickmore et al ., 2021). The complex and challenging nature of school leadership necessitates that principals prioritize learning-centered approaches within their schools (Knapp et al ., 2014).…”
Section: Introductionsupporting
confidence: 73%
“…SMT learning was chosen as a mediating variable in the model because it can enhance sociocognitive processes within teams, which in turn can promote the development of beneficial work norms such as transparency, psychological safety and information sharing, which are critical for improving team functioning and effectiveness (Somech and Naamneh, 2019). This choice aligns with the claim that principals wield significant influence in driving school improvement and implementing transformative changes (Bickmore et al, 2021). The complex and challenging nature of school leadership necessitates that principals prioritize learningcentered approaches within their schools (Knapp et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potential influence, though, few peer-reviewed empirical studies have intentionally investigated SIP templates in general, much less the specific influences SIPs may have on school improvement efforts. The present study is in direct response to both this gap and calls from scholars (e.g., Bickmore et al, 2021;Dunaway et al, 2014) to better describe the SIP development and implementation process.…”
mentioning
confidence: 99%
“…School improvement planning has been a central part of school improvement initiatives for decades (Bickmore et al ., 2021; Tyack and Hansot, 1982). The basic premise has been that principals and school leaders must be strategic in organizing resources and implementing strategies to improve performance.…”
mentioning
confidence: 99%
“…Still, the evidence also indicated that old habits might be hard to break as school leaders did not monitor and adjust plans frequently enough to guide improvement efforts in relative "real time." Keywords Principals, School leadership, School improvement plans Paper type Research paper School improvement planning has been a central part of school improvement initiatives for decades (Bickmore et al, 2021;Tyack and Hansot, 1982). The basic premise has been that principals and school leaders must be strategic in organizing resources and implementing strategies to improve performance.…”
mentioning
confidence: 99%